2009
DOI: 10.1038/nature08616
|View full text |Cite
|
Sign up to set email alerts
|

Transport mechanism of a bacterial homologue of glutamate transporters

Abstract: Glutamate transporters are integral membrane proteins that catalyze a thermodynamically uphill uptake of the neurotransmitter glutamate from the synaptic cleft into the cytoplasm of glial and neuronal cells by harnessing the energy of pre-existing electrochemical gradients of ions. The linchpin of the reaction is the conformational transition of the transporters between outward and inward facing states, in which the substrate binding sites are accessible from the extracellular space and the cytoplasm respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
678
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(719 citation statements)
references
References 48 publications
39
678
0
2
Order By: Relevance
“…A scaffold domain is needed to facilitate the elevator-type movement of the transport domain. The Na + -coupled aspartate transporter Glt Ph is the prototypical example of a transporter that uses this mechanism 72 . d | Hypothetical model for ATPdriven transport by ECF transporters using the toppling mechanism.…”
Section: Transport Mechanismmentioning
confidence: 99%
“…A scaffold domain is needed to facilitate the elevator-type movement of the transport domain. The Na + -coupled aspartate transporter Glt Ph is the prototypical example of a transporter that uses this mechanism 72 . d | Hypothetical model for ATPdriven transport by ECF transporters using the toppling mechanism.…”
Section: Transport Mechanismmentioning
confidence: 99%
“…Structural information is available for the glutamate transporter homolog Glt Ph from the archaeon Pyrococcus horikoshii, which is selective for aspartate rather than glutamate and which couples the uptake of substrate to the symport of three sodium ions [3][4][5][6][7][8] . The protein is a homotrimer, with each protomer consisting of two domains.…”
mentioning
confidence: 99%
“…The trimerization domain mediates the subunit contacts, and the transport domain carries the binding sites for aspartate and sodium ions. Different crystal structures of substrate-bound Glt Ph have revealed that the trimerization domains form a stable scaffold 6,9 . The transport domains have been captured in three states: outward facing, intermediate and inward facing [5][6][7] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is well exemplified by a recent XRC analysis of a functional double mutant of Glt Ph , a glutamate transporter from Pyrococcus horikoshii (Verdon and Boudker, 2012). While previous structure determinations captured Glt Ph (Yernool et al, 2004;Boudker et al 2007) and its analogue (Reyes et al, 2009) as symmetric trimers with all their protomers facing either outward or inward, the structure of the Glt Ph -V198CA380C Hg double mutant is an asymmetric trimer with two protomers in IFS and one in an intermediate outward-facing state (iOFS) (Fig. 4A).…”
Section: E Primary and Secondary Transportersmentioning
confidence: 82%